Nothingness and Time - Tom Boland; Ray Griffin (Temporalités)
Unemployment is not just an economic category but is constituted by governmentality (Foucault, 2010), most evidently by the increase of interventions into the lives of the unemployed through Active Labour Market Policies (ALMP). Furthermore, the International Labour Organization (ILO) definition of unemployment as being without work, available for work and seeking work is a shifting classification which categorises unemployment on multiple temporal horizons, with the passive element of being without work increasingly superseded by the emphasis on seeking work. Through biographical interviews with unemployed in Ireland, spanning from 2012-2018, we trace this transformation of temporality empirically and conclude that governmentality constitutes multiple, contradictory, indefinite forms of time. Particularly, we offer an imaginative reading of two overlapping temporalities: Kairos, waiting, enduring, suffering nothingness in anticipation of transformation by getting a job, and Cronos, not cyclical time, but the devouring of time, where the days and leisure of the unemployed people are deliberately consumed by job-seeking. Ironically, states implement ALMPs in the kairotic hope of transforming their economy, yet these policies do little but make the experience of unemployment even harder to endure.